Moving origins of coordinates - Mahbod, Mohammad (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In the moving (object) origin of coordinates, 2 algebraic relations, 2 differential equations can be compared with each other, and in the each, 2 moving objects relations can be obtained relative to each other. In the issue of the moving (object) origin of coordinates, mentioning some different examples will contribute to the problem understanding.